Wake in Fright Based on a Novel by Kenneth Cook - Kotcheff, Ted; West, Brian; Pleasence, Donald; Bond, Gary; Rafferty, Chips (Eureka Video, 2014)
A legendary "lost film" from 1971, Canadian director Ted Kotcheff’s (First Blood) Aussie psychodrama offers a terrifying picture of rampant masculinity soaked in alcohol and mired in brutality. A fastidious schoolteacher (Gary Bond), heading for Sydney on vacation, loses all his money and finds himself trapped in "the Yabba", an outback hellhole given over to beer-swilling, macho brawling and kangaroo slaughter. His spiral into degradation is abetted by the town cop (Chips Rafferty in his final role) and the boozy local doctor (Donald Pleasence, chillingly deranged). Shocking, credible and hard to forget. [www.totalfilm.com]
Keywords: Blu-Ray-Disc